Effect of a Natural Supplement Containing Curcuma Longa, Guggul, and Chlorogenic Acid in Patients With Metabolic Syndrome. (October 2015) - Patti, Angelo Maria; Al-Rasadi, Khalid; Katsiki, Niki; Banerjee, Yajnavalka; Nikolic, Dragana; Vanella, Luca; Giglio, Rosaria Vincenza; Giannone, Valeria Ausilia; Montalto, Giuseppe; Rizzo, Manfredi
The impact of a natural supplement (Kepar; Rikrea, Italy), containing several plant extracts such as curcuma longa, silymarin, guggul, chlorogenic acid, and inulin, was evaluated in 78 patients with metabolic syndrome (MetS; 45 men; age: 62 ± 9 years). Kepar at a dose of 2 pills/d was given for 4 months as add-on therapy to the ongoing treatment, maintained at fixed doses for the entire study. Anthropometric variables, plasma lipids, glucose parameters, and oxidative stress were measured at baseline and after 4 months. We found significant reductions in body weight (from 81.1 ± 13.5 to 79.4 ± 12.5 kg, P < .0001), body mass index (from 29.6 [23.7] to 29.3 [21.9] kg/m 2, P = .001), and waist circumference (from 105 ± 11 to 102 ± 10 cm, P = .0004) as well as in fasting glucose (from 6.5 [11.7] to 6.4 [7.6] mmol/L, P = .014) and total cholesterol (from 4.8 ± 1.4 to 4.5 ± 1.0 mmol/L, P = .03). No significant changes were found in the other appraised parameters, including oxidative stress. In conclusion, after few months of treatment Kepar seems to exert beneficial effects in patients with MetS. Larger studies with a longer follow-up period are needed to confirm these preliminary findings.